1984
DOI: 10.2169/internalmedicine1962.23.22
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic abnormalities in cerebrovascular accidents.

Abstract: In order to assess the relationship of electrocardiographic (ECG)changes in acute cerebrovascular accidents (CVA)to the locations of the cerebral lesions, ECGrecords and brain computerized tomographic (CT) scans which were taken within 48 hours of CVAonset were examined in 39 patients without heart disease and/or treatment with cardiovascular drugs. The ECGwas normal in 25%(3/12) of basal ganglial CVA, 22% (2/9) of frontal CVAand 36% (4/ll) of temporo-parietal CVA. Nonspecific ST-T changes occurred in basal ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Previous studies showed that repetitive seizures can induce remodeling of the potassium and sodium channels within the heart, leading to QTc prolongation and cardiac arrhythmias [37], and that autonomic neuropathies can prolong QTc interval in patients with primary central nervous system disease [38][39][40][41][42], autonomic neuropathy [43,44], and amyotrophic lateral sclerosis [45]. The exact mechanism by which altered nervous system control leads to cardiac arrhythmias in these cases is unknown.…”
mentioning
confidence: 99%
“…Previous studies showed that repetitive seizures can induce remodeling of the potassium and sodium channels within the heart, leading to QTc prolongation and cardiac arrhythmias [37], and that autonomic neuropathies can prolong QTc interval in patients with primary central nervous system disease [38][39][40][41][42], autonomic neuropathy [43,44], and amyotrophic lateral sclerosis [45]. The exact mechanism by which altered nervous system control leads to cardiac arrhythmias in these cases is unknown.…”
mentioning
confidence: 99%
“…Various ECG abnormalities are to be expected in patients with cerebral diseases. [1][2][3][4][5][6][7] Rhythm disturbances and altered repolarization in the ECG, such as QT prolongation, are the most frequent findings. It is hypothesized that these ECG abnormalities are mediated by the central nervous system as a result of the cerebrovascular event.…”
mentioning
confidence: 99%
“…[2][3][4] The few that include thromboembolic events consider thromboembolic stroke and subarachnoid hemorrhage to be a single entity despite obvious pathophysiologic differences. Few reports [5][6][7] distinguished between these two diseases and compared changes in QT interval and other ECG abnormalities. Similar to hemorrhage, QT prolongation is seen most frequently among patients with thromboembolic stroke.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities that appear most frequently during the thromboembolic stroke are prolonged QT interval and ST-T wave changes. [5][6][7] All studies on QT interval changes in stroke patients refer to the QT interval measured once at a determined heart rate and mostly at resting heart rates. Since QT length changes with heart rate, its values can be compared only after correction to a common rate, and the Bazett heart rate corrected QT (known as QT c ) is used.…”
mentioning
confidence: 99%